BIOECONOMIC PRINCIPLES OF AGROTECHNOLOGY DESIGN IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND FOOD SECURITY OF UKRAINE - Kovalenko, Vladyslav; Bashlai, Serhii (European Science, 2025)
The research paper is devoted to the study of bioeconomic approaches to the design of sustainable development technologies in the agricultural sector of production as part of ensuring food security in Ukraine. The aim was to study approaches to solving th